(untitled) (Raparin Journal of Humanities (RJH), 2020)
streets are one of the most important ways of using ground in cities because it’s away to connect living areas and delivering the best service possible and doing numerous activities that are done in the cities because of that street need to be built only using the best materials and the best qualities to be the most useful for citizens and people of the cities so the roads need to suit the growth and expansion of the cities and they’re so in this research we talk about the steps of building and growing streets However we try to create street in all municipal ideally they elastic with circumstance economic , political ,population.